Effect of Freeze–Thaw Cycles on the Flexural Strength of Greek Natural Stones - Konstantinos Laskaridis; Angeliki Arapakou; Michael Patronis; Christos Papatrechas; Ioannis Kouseris (Materials Proceedings, 2024)
The purpose of this study is to explore the potential influence of cyclic freezing–thawing on the flexural strength of Greek natural stones that are extensively utilized for construction or decoration purposes. Such testing approaches are an indispensable part of the stone selection criteria due to their ability to assess the stone’s durability. It is especially crucial in locations where exposure to freeze–thaw cycles is common. For this study, samples from various types of stones, including limestones, calcite and dolomite marble, cipollino marble, schists, and mylonites, were examined to assess their flexural strength under concentrated loads and their associated values after freeze–thaw cycles in compliance with European standards (EN). The results show that stones of the same type have comparable flexural strength behaviour. Only in a few cases were significant increases or decreases in strength observed. Specific stones demonstrated a substantial reduction in their flexural strength when exposed to freeze–thaw cycling despite their initially calculated high values without having undergone the frost durability test.